Bringing Finance to Pakistan's Poor : Access to Finance for Small Enterprises and the Underserved - Nenova, Tatiana; Thioro Niang, Cecile; Ahmad, Anjum (Washington, DC: World Bank, 2013)
Access to financing is now widely acknowledged as a path to meaningful economic inclusion and reduction in poverty. Policy efforts to increase access to finance in Pakistan have taken time to bear fruit, but now access is indeed expanding quickly in certain financial sectors (microfinance, remittances), albeit from a very low base. Nevertheless, policy measures cannot single-handedly increase financial access; financial institutions' willingness to expand access in Pakistan has been stinted by slow technologic advances, weak legal foundations, and unsuitable financial processes and products. Poor socioeconomic conditions, gender bias, and low levels of basic education and financial literacy remain barriers, but perhaps the single strongest driver of low demand for financial access has been income. The primary purpose of this study is to measure and describe the state of financial service provision to underserved segments of the market in Pakistan, particularly those with low incomes and small enterprises, and to identify ways to improve investment and create inclusive markets that meet the needs of underserved people and enterprises.